Is CRISPR/Cas9 a way forward to fast-track genetic improvement in commercial palms? Prospects and limits - Khan, Faiza Shafique; Goher, Farhan; Zhang, Dapeng; Shi, Peng; Li, Zhiying; Htwe, Yin Min; Wang, Yong (Frontiers in Plant Science, 2022)
Commercially important palms (oil palm, coconut, and date palm) are widely grown perennial trees with tremendous commercial significance due to food, edible oil, and industrial applications. The mounting pressure on the human population further reinforces palms’ importance, as they are essential crops to meet vegetable oil needs around the globe. Various conventional breeding methods are used for the genetic improvement of palms. However, adopting new technologies is crucial to accelerate breeding and satisfy the expanding population's demands. CRISPR/Cas9 is an efficient genome editing tool that can incorporate desired traits into the existing DNA of the plant without losing common traits. Recent progress in genome editing in oil palm, coconut and date palm are preliminarily introduced to potential readers. Furthermore, detailed information on available CRISPR-based genome editing and genetic transformation methods are summarized for researchers. We shed light on the possibilities of genome editing in palm crops, especially on the modification of fatty acid in oil palm. Moreover, the limitations in genome editing, including inadequate target gene screening due to genome complexities and low efficiency of genetic transformation, are also highlighted. The prospects of CRISPR/Cas9-based gene editing in commercial palms to improve sustainable production are also addressed in this review paper.